A Model to Describe the Dynamic Influence Length of the Vehicles on the Main Road at the Upstream Sections of Off-Street Parking Access. (29th December 2013) - Shejun, Deng; Jun, Chen
Abstract : We research into the upstream sections of off-street parking access in the city. When the parking car turns right from the main road of the rightest lanes into the access, the vehicles which are the upstream of the access on the main road may be affected and the influence length can be presented as two parts: one is the deceleration distance of the parking car and the other is the propagation distance of traffic wave caused by the following vehicles. By the way of theoretical analysis and field investigation, we present a model that represents the dynamic influence length under the condition of different entering time and moderate saturation. Parameters were specialized to represent the characters of parking car and the vehicles following it, including park entering time and speed variation rate. Some conclusions were drawn by contrasting the simulation of VISSIM 5.3 and the model. First, when entering time was between 4 s to 8 s, saturation and the influence length were in inverse proportion; while the entering time was more than 8 s, saturation and the influence length were in direct proportion. Second, when the saturation was between 0.46 and −0.5 and entering time was between 4 s and 15 s, parking car had no effect on the vehicles. Third, when the saturation was more than 0.6 and entering time was more than 9 s, the effect of parking car on the vehicle's influential length increased significantly.